2012
DOI: 10.5812/iranjradiol.7561
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Infection Rate Following Use of Povidone-Iodine During Transrectal Ultrasound Guided Biopsy of the Prostate: A Double Blind Randomized Clinical Trial

Abstract: BackgroundInfection after transrectal ultrasound (TRUS) guided biopsy of the prostate is a major and potentially life-threatening problem. Using antibiotic premedication can not completely eliminate infection after biopsy.ObjectivesWe performed this study to determine the value of using povidone-iodine in prevention of post biopsy infection.Patients and MethodsTotally, 280 patients who were referred for TRUS guided biopsy of the prostate were divided randomly into two equal groups. The case group received an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…In case of rectal cleansing, different implementations were used in some studies. Ghafoori et al [22] divided 280 patients who were scheduled to undergo TPB, randomly into two equal groups. The case group received an intrarectal mixture of povidone-iodine and lidocaine gel before the biopsy and the other group received only lidocaine gel.…”
Section: Discussionmentioning
confidence: 99%
“…In case of rectal cleansing, different implementations were used in some studies. Ghafoori et al [22] divided 280 patients who were scheduled to undergo TPB, randomly into two equal groups. The case group received an intrarectal mixture of povidone-iodine and lidocaine gel before the biopsy and the other group received only lidocaine gel.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the EAU guidelines recommend to use rectal cleansing with povidone-iodine prior to transrectal PB [5]. This is based on a meta-analysis of six trials including 1373 men that showed that the use of pre-biopsy rectal povidone-iodine preparation in addition to antimicrobial prophylaxis resulted in lower rates of infectious complications [0.58 (0.43 to 0.76); RR (95% CI)] [22][23][24][25][26][27]. However, not a single Dutch urologist reported to use rectal povidone-iodine cleansing prior to PB.…”
Section: Fig 3 Urologists' Perception Of Antimicrobial Prophylaxis Imentioning
confidence: 99%
“…Furthermore, tumoricidal irrigants may be of added value, and it is generally recommended to irrigate before and after purse-string construction. [20][21][22][23][24] Extraction and Ischemia of the Conduit Extraction and anastomotic complications can also be observed, including stress and shear strain from (when employed) transanal extraction that could lead to conduit ischemia. 1 To avoid shear stress from transanal extraction, it is recommended to deliver a bulky mesentery via an abdominal extraction site, and not via the anus.…”
Section: Purse-string Disruptions and Aerosolized Cellsmentioning
confidence: 99%